Riski saistībā ar Spānijas nekustamo īpašumu diskontētu parāda ieguldījumu privātajiem investoriem - Bohnenblust, David (Latvijas Universitāte, 2024)
.

Discounted Debt Investments are a misunderstood and fairly new product as an investment opportunity. Due to this fact, retail investors face struggles in both understanding the product and protecting themselves from risks associated with the product. This bachelor’s thesis, “Risks of Spanish Real Estate Discounted Debt Investment For Retail Investors” aims to make an assessment of risk in order to create information for retail investors on the risks associated with real estate discounted debt investment in the Spanish financial market and ways to mitigate them. In the third chapter of this thesis, the author conducted interviews with industry experts in order to better achieve the goal of this thesis. This included the director of a Non-performing loan servicing company located in Spain and the Chief of Operations of an investment company which is currently the lone spanish discounted debt investment provider on the market. The findings of this thesis were to use the foundational investment theories of Samuelson and Merton, to implement strong risk management practices, to stay informed on any market updates and trends, to evaluate the risks associated with Spain's regulatory environment, and to consider testing out the Indemo platform . The thesis consists of 63 pages, 7 figures, 3 tables, and 5 appendices.
Risks of Spanish Real Estate Discounted Debt Investment for Retail Investors
Keywords: Ekonomika un uzņēmējdarbība; Risks; Real Estate; Discounted Debt; Non-performing loans; Investment